The Effect Of Work Environment On Job Satisfaction Is Mediated By Burnout - Asmanto, Danny; Taufik, E. R.; Kambara , Roni (Advances In Social Humanities Research, 2025)
Human resources in an organization are a crucial aspect that determines a company's effectiveness. One of the primary concerns of a company is the work environment, which significantly impacts employee job satisfaction. A good work environment can provide a comfortable impression for employees to carry out their work and can reduce employee boredom at work. This type of research uses a survey research method. The research sample was 80 respondents. Data collection techniques were carried out through Literature Study, Field Research such as Observation, Interviews, Documentation, and Questionnaires. In this study, data analysis used structural equation modeling, often referred to as Structural Equation Modeling (SEM). In this study, an approach was used using Partial Least Square (PLS). The results of this study indicate that the work environment influences job satisfaction, the work environment influences job satisfaction mediated by burnout, and burnout influences job satisfaction.